Evaluation of antioxidant and antimicrobial potency of stem of entada spiralis / Nur Khairunnisa' Maha Yudden - Maha Yudden, Nur Khairunnisa' (Faculty Of Applied Sciences, 2019)
Entada spiralis known as 'Beluru' or 'Sintok' which is from Leguminosae family was used in this research to determine the antioxidant and antimicrobial properties. This plant was known to contain chemical substances which are phytochemical or also known as secondary metabolites and have been used to treat disease and as health care. In determining antioxidant and antimicrobial properties, several methods were conducted. The stem of E.spiralis was extracted using four different polarities of solvents such as petroleum ether, dicholoromethane, ethyl acetate and methanol. Phytochemical screening on TLC using certain spraying reagent, FTIR analysis, dot blot assay, radical scavenging activity and disc diffusion method was conducted to evaluate antioxidant and antimicrobial potency of E.spiralis. From the phytochemical screening test, it has been screened that stem of E.spiralis contained terpenoids, saponins and leucoanthocyanins. From the antimicrobial study of disc diffusion method, EA extract are the most active extract with the largest inhibition zone of 19 mm towards Erwinia sp. From the result of dot blot assay, EA extract is the most antioxidative extract which showed the highest intensity of white colour compared to the other extract. In the radical scavenging activity, standard ascorbic acid (IC50 9 µ.g/mL), exhibited the strongest scavenging activity compared with other extracts followed with methanol extract (IC50 11 µ.g/mL), ethyl acetate (IC50 13 µ.g/mL) and petroleum ether (IC50 42 µ.g/mL) extracts. While the DCM extract has high IC50 values of more than 100 µ.g/mL. This study has finally achieved its objectives by focusing on screening phytochemicals, evaluating antioxidant and antimicrobial properties from stem of E.spiralis.